ANALYSIS OF METHODOLOGICAL ERRORS OF THE AVIATION GRAVIMETRIC SYSTEM WITH A TRANSFORMATON GRAVIMETER - BEZVESILNA, OLENA; NECHAI, SERGEY; TOLOCHKO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The equations of motion and a list of the main components of the AGS are given: gravimeter, stabilization system, system for determining navigation parameters, height meter, on-board digital computer. An analysis of methodological errors of the aviation gravimetric system with a transformer gravimeter was carried out, from which the accuracy requirements for the AGS components were formulated, provided that the accuracy of PST measurements is 1–2 mGal Analytical expressions were found and the coefficients of sensitivity of the total error of the AGS output signal to the measurement errors of the following aircraft movement parameters were calculated: speed, course, latitude, altitude, vertical speed, vertical acceleration, path for different flight modes. Therefore, the study of the sensitivity of the AGS to errors in the measurement of speed, latitude and course, depending on a number of parameters of the aircraft movement, showed that in the case of aviation gravimetric measurements along the Earth’s meridian, it is necessary to accurately determine the course, along the Earth’s parallel - to accurately measure the speed, in mid-latitudes - latitude . It is substantiated that the use of a new two-channel transformer gravimeter provides the necessary increase in the accuracy of AGS. Changes in the sensitivity of the error of the AGS output signal to speed measurement errors were studied depending on the latitude of the site at constant values of the course, as well as on the course of the aircraft at constant values of the latitude. It is shown that the sensitivity of the AGS to speed measurement errors is maximum for the east and west courses (22.6 mGl/m/s and - 6.5 mGl/m/s, respectively) at the location latitude j= 00; minimum for north and south courses and at j=900 regardless of the course (8.05 mGl/m/s). Permissible values of errors in determining the flight parameters of the aircraft were calculated: speed 0.05...0.15 m/s, heading 1.43...3 arcmin, latitude 0.5...1.5 arcmin. min., height 3.3...10 m, vertical speed (0.5...1).102 m/s, vertical acceleration (1...3).10-5 m/s2, path (1.5...4.5) m.